Management of sepsis in neutropenic cancer patients: 2018 guidelines from the Infectious Diseases Working Party (AGIHO) and Intensive Care Working Party (iCHOP) of the German Society of Hematology and Medical Oncology (DGHO) - Kochanek, Matthias; Schalk, Enrico; Bergwelt-Baildon, Michael von; Beutel, Gernot; Buchheidt, Dieter; Hentrich, Marcus; Henze, Larissa; Kiehl, Michael G.; Liebregts, Tobias; Lilienfeld-Toal, Marie von; Classen, Annika; Mellinghoff, Sibylle Christiane; et al. (Annals of hematology, 2019)
Sepsis and septic shock are major causes of mortality during chemotherapy-induced neutropenia for malignancies requiring urgent treatment. Thus, awareness of the presenting characteristics and prompt management is most important. Improved management of sepsis during neutropenia may reduce the mortality of cancer therapies. However, optimal management may differ between neutropenic and non-neutropenic patients. The aim of the current guideline is to give evidence-based recommendations for hematologists, oncologists, and intensive care physicians on how to manage adult patients with neutropenia and sepsis.
Gesehen am 20.05.2019